1981
DOI: 10.1902/jop.1981.52.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Palato‐Gingival Grooves to Localized Periodontal Disease

Abstract: The purpose of this investigation was to determine the prevalence of the palato-gingival groove in maxillary incisor teeth and the health status of the lingual periodontal tissues adjacent to maxillary incisor teeth with and without the grooves. A total of 531 individuals aged 17 to 35 years were examined for the presence or absence of palato-gingival grooves in their maxillary incisor teeth. A Plaque Index (PII), Gingival Index (GI), and Periodontal Disease Index (PDI) were recorded for the lingual aspect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
114
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 5 publications
8
114
0
8
Order By: Relevance
“…Anatomically, the upper arch incisors usually present the palatal gingival groove (lateral: 4.40% and central: 0.28%) 54) , which is considered to be a risk area for periodontal disease 15) , since the groove may provide a niche for plaque and bacteria difficult to access during scaling. Therefore, the probability of early tooth loss is higher in the upper arch than in the lower arch incisors 17) .…”
Section: Resultsmentioning
confidence: 99%
“…Anatomically, the upper arch incisors usually present the palatal gingival groove (lateral: 4.40% and central: 0.28%) 54) , which is considered to be a risk area for periodontal disease 15) , since the groove may provide a niche for plaque and bacteria difficult to access during scaling. Therefore, the probability of early tooth loss is higher in the upper arch than in the lower arch incisors 17) .…”
Section: Resultsmentioning
confidence: 99%
“…Not all grooved teeth will present a breakdown of the epithelial attachment, but the presence of the anomaly constitutes a risk factor of which the dentist should be aware. Whithers et al 11) reported that the palato-gingival groove is associated with a "poor periodontal health." Unfortunately, the "poor periodontal health"combined with a deep groove may put the tooth at risk, with poor prognosis 12) , despite periodontal and endodontic treatment [13][14][15] .…”
Section: ⅲ Discussionmentioning
confidence: 99%
“…The usage of this trait in anthropologic studies indicates its racial link [6]. The incidence of radicular groove is reported to be between 2.8% and 18% [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%